No Own-Age Bias in Children’s Gaze-Cueing Effects - van Rooijen, Rianne; Junge, Caroline; Kemner, Chantal (Frontiers in Psychology, 2018)
Sensitivity to another person’s eye-gaze is vital for social and language development. In this eye-tracking study, a group of 74 children (6-14 years old) performed a gaze cueing experiment in which faces cued the location of a peripheral target. The aim of the present study is to investigate whether children’s gaze cueing effects are modulated by the other person’s age. In half of the trials the gaze cue was given by adult models, in the other half of the trials by child models. Regardless of the models’ ages, children displayed an overall gaze cueing effect. However, results showed no indication of an own-age bias in the performance on the gaze cueing task; the gaze cueing effect is similar for both child and adult face cues. These results did not change when we looked at the performance of a subsample of participants (n = 23) who closely matched the age of the child models. Our results do not allow us to disentangle the possibility that children are insensitive to a model’s age or whether they consider models of either age as equally informative. Future research should aim at trying to disentangle these two possibilities.